Reliability and validity of patient-reported outcomes measurement information system® (PROMIS®) measures of pain in adult males with hemophilia - Tyler W. Buckner; Dianne Thornhill; Bryce B. Reeve; Thomas A. Wilkinson; Sonia Nasr; Marilyn J. Manco-Johnson (Journal of Patient-Reported Outcomes, 2026)
Abstract Background Inadequate pain assessment in persons with hemophilia (PwH) can lead to undertreatment of hemophilia-related pain. Effective pain management in PwH is limited by the lack of valid, reliable pain assessment tools that can be readily incorporated into clinical practice. The objectives of this study are to evaluate the reliability and validity of the Patient-Reported Outcomes Measurement Information System ® (PROMIS ® ) pain intensity, interference, and behavior measures in PwH. Methods PROMIS pain measures were evaluated in a cross-sectional study that consecutively enrolled males ages ≥ 18 years with hemophilia A or B during routine clinical visits. Participants provided responses to static short forms (for the pain intensity domain) or to computerized adaptive tests (for pain interference and pain behavior domains) using electronic devices. Content validity was assessed through one-on-one interviews. Reliability (internal consistency and test-retest reliability), known group validity, and convergent validity were also evaluated. Results Responses to PROMIS pain measures were collected from 150 participants. Content validity for the PROMIS pain interference item bank was good, with no coverage gaps identified in eight one-on-one interviews. Internal consistency for PROMIS pain measures was high (marginal reliability ranging between 0.87 and 0.91), and PROMIS pain measures showed adequate test/retest reliability over 24–72 h (intraclass correlation coefficients 0.85–0.95). We observed strong to very strong correlations between PROMIS measures and Brief Pain Inventory and Short Form-36 pain subscales (Pearson correlation coefficient magnitudes of 0.66–0.88), indicating convergent validity for these measurements. Conclusions Results from this cross-sectional study support the reliability and validity of PROMIS pain intensity, interference, and behavior measures when assessing patient-reported pain in male PwH.